Dementia and human rights - Cahill, Suzanne (Bristol, UK : Policy Press, 2018)
Launching the dementia debate into new and exciting territory, this book applies a human rights lens to interrogate the lived experience and policy response to dementia.
An introduction to human rights and dementia -- Dementia as a disability -- Setting the context: The UN convention on the rights of persons with disabilities -- The right to a good quality of life at home and in the community -- The right to a good quality of life in care homes or in nursing homes -- Emerging public policy on dementia: the implications of a human rights-based approach for policy and practice -- Legal capacity for people with dementia: a human rights approach -- Conclusions: grounds for hope
Includes bibliographical references (pages 189-232) and index.
In English.
JSTOR
Keywords: Dementia -- Patients -- Legal status, laws, etc; Mental health laws; Human rights; Dementia; Human Rights; Droits de l'homme (Droit international); LAW -- Administrative Law & Regulatory Practice; Human rights; Mental health laws; Menschenrecht; Demenz; Electronic book